Social Movement Intersectionality and Re-Centring Intersectional Activism - Broad, K.L. (Atlantis, 2017)
In this paper, I argue that intersectional activism needs to be re-centered in intersectional studies and that research about social movement intersectionality offers one means of doing so. To demonstrate this argument, I review several examples that complicate our understanding of how social movement intersectionality is done in practice. I discuss how these examples reiterate the point that intersectional movements can be realized; illustrate how coalitions are varied but do work; and remind us that there are, nevertheless, unique constraints that those striving to do social movement intersectionality face—for example, the challenge of constructing critical collective consciousness. I close by discussing analytic strategies characterizing the emerging research on social movement intersectionality and lessons offered herein and I call for deeper inquiry to engage activist work and re-center activist knowledges in intersectionality studies.